FACTORS RELATED TO MEDICATION MANAGEMENT AT SIMPANG TIGA HEALTH CENTER SIMPANG THREE DISTRICT - Nur Akmal (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
One of the essential things in health services is the management and financing of medicines. The data that researchers obtained showed that one of the problems was the lack of stock of medicines in health installations, giving medicines to patients close to the expiry date. Sometimes, the medicines given to patients were not appropriate. This research aims to determine the factors related to the drug management system at the Simpang Tiga Community Health Center in 2023. The research method used was analytical descriptive with a cross-sectional study approach and the chi-square test. The sample was 32 people, carried out on January 22 - January 27, 2023, at Simpang Tiga Health Center. The data collection tool is a questionnaire consisting of 30 statement items which have been tested for validity and reliability. Research Results: Planning with a good drug management system (69%) (p = 0.028), there is a relationship between procurement and a sound drug management system (80%) (p = 0.015), there is a relationship between storage and a good drug management system (73 .1%) (p= 0.015), there is a relationship between distribution and a good drug management system (81.8%) (p = 0.001), there is a relationship between recording and reporting with a good drug management system (71.4%) (p = 0.010).